Penguatan Sikap Positif Perempuan Kristen dalam Keluarga, Gereja dan Masyarakat - Audra Jovani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
The state is obliged to protect its citizens, both men and women in various aspects of life, including in the family as the smallest part, and in the church community and in society as the largest part. Women and men also have the same position in all fields that have access, participation, control and benefits from development for themselves and their families. The church as a spiritual community is an important place to develop spiritual and social life for women and men. However, women often think that the church is only a place for personal life between their self and God, even though in fact the church can be a place or community that is able to give women access, participation, control and benefits for their lives as individuals and as a group. In addition, in the church community, women can develop abilities and positive attitudes within themselves, their families and their environment. Through this community service activity, the head proposer and other members raise women's awareness about the importance of women having a positive attitude in the family, church and society. Women have the opportunity and are able to play a big role for themselves, their families, the church and society. This activity was held on Saturday, 30 July 2022 at HKBP Filadelfia Bekasi Church with 80 congregation members consisting of women and men. This activity begins with awareness and dissemination of the importance of a positive attitude of Christian women in the family, church and society. Through this activity, the awareness of women and men members of the congregation to be able to have a positive attitude in all aspects of life arises. Keywords: positive attitude; Christian women; family; church; public.